Astragalus unalii (Fabaceae), a new species from Turkey - Çeçen, Ömer; Aytaç, Zeki; Mısırdalı, Hüseyin (Turkish Journal of Botany, 2016)
Astragalus unalii Çeçen, Aytaç and Mısırdalı, sp. nov. (Fabaceae, sect. Malacothrix Bunge) is described as a new species from Karadağ (Karaman Province) in southern Anatolia and compared with its relatives growing in steppe vegetation. The new species is close to A. tauricola Boiss. and A. adiyamanensis Podlech & M.Ekici, endemic and growing in central and southern parts of Anatolia, Turkey. Taxonomic descriptions, pollen and seed characters, and geographical distribution of the new species are presented.
Keywords: Leguminosae; Malacothrix; Systematics